Cardioprotective effect of 2',3,4'- trihydroxychalcone in preclinical experiment - Bartošíková, Lenka; Nečas, Jiří; Bartošík, Tomáš; Pavlík, Martin; Perlík, Vít (Česká a slovenská farmacie, 2009)
2',3,4'-trihydroxychalcone is a newly synthesized substance with antioxidant properties. The aim of this pilot study was to monitor its effect during heart perfusion in the laboratory rat. The study included two groups of animals of the same number (n = 10). The 1st group was pretreated with chalcone in a dose of 10 mg/kg p.o. during 15 days. The 2nd group was a placebo one. After i.p. administration of a heparin injection of 500 IU dose, the hearts were excised and perfused (a modified Langendorf's method). Working schedule: stabilization/ischaemia/reperfusion proceed at intervals of 20/30/60 min. Monitored parameters in the isolated heart: left ventricle pressure (LVP), end-diastolic pressure (LVEDP), contractility (+dP/dtmax). The treated hearts showed improved postischemic recovery, reaching LVP values of 101 ± 4% at the end of reperfusion, the placebo ones only 42 ± 6%. In the placebo hearts LVEDP increased from 10.0 ± 0.5 mm Hg to 32 ±5 mm Hg after, in treated animals only about 10.5 ± 2 mm Hg. The treated hearts improved +dP/dtmax recovery during reperfusion to 92 ± 7 %. These values were significantly greater than those obtained from the placebo hearts. We conclude that the administration of 2',3,4'-?-trihydroxychalcone in laboratory rats has a cardioprotective potential against ischemia-reperfusion induced injury.
Keywords: chalkonoidy; preklinické hodnocení léčiv; potkani Wistar; modely u zvířat; zvířata; Models, Animal; Drug Evaluation, Preclinical; Rats, Wistar; Animals; Myocardial Reperfusion Injury; Chalcones; reperfuzní poškození myokardu